Analisis Ketahanan dan 8 Fungsi Keluarga di Provinsi Jambi Serta Faktor-Faktor yang Mempengaruhinya - Fachroerrozi Hoesni; Firmansyah Firmansyah (Universitas Batanghari Jambi, 2020)
For the implementation of 8 family functions in Jambi Province, the majority of families in Jambi Province (86.60%) do not know about 8 family functions. The implementation of 8 family functions in Jambi Province was the most (43.82%) enough categories, religious functions, socio-cultural functions, love functions, protection functions, reproductive functions, socialization and education functions, economics, and environmental functions in urban families and Jambi Province villages are different except for environmental functions. For the activeness of family resilience in Jambi Province, it can be concluded that the majority of families in Jambi Province are unaware of the Tribina Activity Group (BKB, BKR, BKL), PIK R / M, UPPKS and PPKS. The higher the education of family heads, the higher the implementation of 8 family functions in Jambi Province.